Fumante passivo e perda auditiva em pré-escolares e escolares: estudo caso-controle - Raquel Nobre Monteiro; Adauto Dutra Moraes Barbosa; Licínio Esmeraldo da Silva (Sociedade Brasileira de Pediatria, 2023)
INTRODUCTION: Nonsmoking individuals who live with indoor smokers are included among those at higher risk of hearing loss, as the inner ear is sensitive to systemic changes, especially vascular ones. OBJECTIVE: To investigate whether there is an association between passive smoking and hearing loss in preschoolers and school-aged children. METHOD: retrospective, descriptive, case control study, comprising 76 children between 2 and 10 years of age, who underwent audiometric assessment between January 2016 and December 2018. The included children were divided into two groups: passively exposed to tobacco and not exposed to tobacco. The association between exposure or not to tobacco and type of hearing loss was evaluated using Fishers exact test, and the odds ratio of hearing loss in exposed children was calculated. RESULTS: Children exposed to smoking had fourfold odds of hearing loss compared to their non-exposed peers (OR 4.2, 95%CI 1.584 to 11.138). A significant association was also observed between exposure to smoking and sensorineural hearing loss (OR 5.60, 95%CI 1.783 to 17.591, p=0.002). No association was found between severity of exposure and intensity of hearing loss. CONCLUSION: This study suggest that sensorineural hearing loss occurs more frequently in children exposed to smoking then in their age-matched peers not so exposed. However, we cannot state conclusively whether there is an association between passive smoke exposure and conductive hearing loss, nor between the degree of hearing loss and the level of exposure to nicotine as assessed by the Fagerström test.